No association between polymorphisms in the INSIG1 gene and the risk of type 2 diabetes and related traits. - Szopa, M; Meirhaeghe, A; Luan, J; Moreno, L; Gonzalez-Gross, M; Vidal-Puig, A; Cooper, C; Hagen, R; Amouyel, P; Wareham, N; Loos, R (2010)
BACKGROUND: The insulin-induced gene 1 (INSIG1) encodes a protein that blocks proteolytic activation of sterol regulatory element binding proteins, which are transcription factors that activate genes that regulate cholesterol, fatty acid, and glucose metabolism. OBJECTIVE: We tested for associations between 6 INSIG1 tag single nucleotide polymorphisms (SNPs) (and captured all common variations in INSIG1) and the risk of type 2 diabetes (T2D), obesity, and related traits in 10,567 adults and 1155 adolescents from 5 population-based studies, a T2D case-control study, and a T2D case-series. DESIGN: We genotyped tag SNPs and tested them for associations with the risk of T2D or obesity and with body mass index, waist circumference, systolic and diastolic blood pressure, and concentrations of fasting glucose, 2-h oral-glucose-tolerance test glucose, cholesterol, and triglyceride, with the assumption of an additive effect of the minor allele. Dominant effects were tested for the less-frequent SNPs (minor allele frequency <5%). Summary statistics of each study underwent meta-analysis. RESULTS: Meta-analyses, which included 1655 T2D cases and 2911 control subjects, showed no association between any of the INSIG1 SNPs and T2D (P > 0.08). Furthermore, none of the SNPs showed an association with obesity in 1666 obese and 5737 nonobese individuals (P > 0.17). In agreement, none of the associations between the SNPs and any of the metabolic traits showed convincing associations in the 7562 adults from 4 population-based studies. Although a few nominally significant associations emerged, none of the associations survived multiple-testing correction. We observed no convincing associations with any of the studied traits in 1155 adolescents. CONCLUSION: Although our study was sufficiently powered to identify small effects, the results suggest that common variation in INSIG1 is unlikely to have a major effect on T2D and obesity risk and related traits in white Europeans.